Interaction Effect of Two Instructional Strategies and Mental Ability on Students’ Achievement in Abstract Concepts in Biology - ADEWUMI, Gabriel Segun; ADEOYE, Gabriel Ademakinwa (Ilorin Journal of Education, 2023)
This study determined the interaction effect of two instructional strategies (Project and Inquiry) and mental ability on students’ achievement in abstract concepts in Biology. The pretest-posttest control group, quasi-experimental design was adopted for the study. 120 SSII Biology students from six co-educational schools in two Local Government Areas of Kwara State were randomly assigned to treatment groups. The instruments used were: The abstract Concepts in Biology Achievement Test (r=0.86), Biology Students Mental Ability Test (r=0.87), and Teachers’ Instructional guides on Project and Inquiry strategies. The research questions were answered while the hypotheses were tested using Analysis of Covariance at 0.05 level of significance. The 2-ways interaction effect of treatment and mental ability on students’ achievement in abstract concepts in biology was significant F(2, 107) = 3.006, P > 0.05, partial η2 =0.053). The low mental ability students exposed to project strategy had the highest post-achievement means score (24.28), followed by low mental ability students exposed to inquiry strategy (21.42), high mental ability students in the project strategy (20.22), high mental ability students in the inquiry strategy (17.15), and high mental ability students exposed to conventional strategy (17.29), while low mental ability students exposed to conventional strategy (16.88) had the lowest posttest achievement in abstract concepts in Biology. Thus, the interaction is disordinal. Based on the findings, project and inquiry strategies should be adopted for the improvement of student’s mental ability and achievement in abstract concepts in biology.